P067 Human colonic subepithelial myofibroblasts from IBD patients demonstrate a differential expression of Th-related cytokine receptors compared with healthy controls. (25th January 2019) - Bamias, G; Filidou, E; Valatas, V; Drygiannakis, I; Arvanitidis, K; Vradelis, S; Kouklakis, G; Kolios, G
Abstract: Background: Crohn's disease (CD) and ulcerative colitis (UC) are the two major forms of inflammatory bowel diseases (IBD) and are characterised by chronic and relapsing/remitting inflammation of the intestinal tract that may ultimately lead to fibrosis. Subepithelial myofibroblasts (SEMFs) play a key role in fibrogenesis, as they have been found to produce excessive collagen quantities or enzymes lysing the extracellular matrix (ECM). The aim of the study was to examine whether SEMFs isolated from patients with IBD present different expression patterns of Th-related cytokine receptors compared with healthy controls. Methods: SEMFs were isolated from endoscopically obtained colonic biopsies from healthy controls and IBD patients (CD and UC: CD-SEMFs, UC-SEMFs), set to culture and total RNA was extracted. Cytokine receptors mRNA expression was assessed with reverse transcription quantitative (RT-q) PCR. Results: Unstimulated SEMFs had a basal expression of most of the studied cytokine receptors. As to Th1-related receptors, both CD- and UC-SEMFs expressed reduced levels of IL1R1 (CD: median 0.43-fold, IQR 0.31–0.51, UC: median 0.15-fold, IQR 0.15–0.16) and TNFRSF1A (CD: median 0.39-fold, IQR 0.38–0.51, UC: median 0.27-fold, IQR 0.25–0.29), but presented different expression patterns for IL12RB2; CD-SEMFs expressed reduced levels, while UC-SEMFs increased (CD: median 0.59-fold, IQR 0.48–0.6, UC: median 1.46-fold, IQR 1.44–1.51). As to Th2-related receptors, only UC-SEMFs expressed reduced mRNA levels of IL4R (median 0.24-fold, IQR 0.22–0.25) and IL13RA2 (median 0.23-fold, IQR 0.16–0.26). Concerning the Th17-related receptors, only CD-SEMFs expressed reduced levels of IL17RA (median 0.58-fold, IQR 0.5–0.78), while both CD- and UC-SEMFs were found to express reduced levels of IL23R (CD: median 0.4-fold, IQR 0.28–0.43, UC: median 0.58-fold, IQR 0.57–0.59). Finally, regarding the Treg-related receptors, CD-SEMFs expressed reduced levels of IL10RA (median 0.4-fold, IQR 0.32–0.55) and IL10RB (median 0.53-fold, IQR 0.39–0.65), while UC-SEMFs of TGFBRB2 (median 0.48-fold, IQR 0.34–0.63) and IL10RB (median 0.54-fold, IQR 0.5–0.59). Conclusions: These data suggest that SEMFs might be a dynamic crosslink between the inflammatory and the fibrotic process, as they express most of the Th-related cytokine receptors. CD-SEMFs appear to have reduced expression levels of Th1- and Th17-related cytokine receptors, while in UC-SEMFs, Th2-related cytokine receptors were found down-regulated.